2014
DOI: 10.1200/jco.2014.32.4_suppl.278
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after high-dose rate brachytherapy monotherapy for prostate cancer.

Abstract: ARTICLE INFO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…In our study, 57/82 patients (69.5%) completed the EORTC questionnaire. This rate is acceptable and comparable to Contreras et al [25], who reported 64/84 (76.2%) and others with reported compliance rates of 36% to 78% [22,29].…”
Section: Hrqol and Toxicity Rates After Hdr-bt For Hr Pcasupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, 57/82 patients (69.5%) completed the EORTC questionnaire. This rate is acceptable and comparable to Contreras et al [25], who reported 64/84 (76.2%) and others with reported compliance rates of 36% to 78% [22,29].…”
Section: Hrqol and Toxicity Rates After Hdr-bt For Hr Pcasupporting
confidence: 89%
“…Contreras et al [25] used the Expanded Prostate Cancer Index Composite (EPIC) in their study to assess QoL after HDR-BT. Six months after treatment, they found a significant decrease (p<0.05) in urinary, bowel, and sexual scores, including urinary overall, urinary function, urinary bother, urinary irritative, bowel overall, bowel bother, sexual overall, and sexual bother scores.…”
Section: Discussionmentioning
confidence: 99%
“…We also utilized SHIM and IPSS questions to evaluate changes in urinary and sexual function as these were standard questionnaires given to patients in our clinic. Ideally, our results would have incorporated the more accepted and validated Expanded Prostate Cancer Index Composite, which has been considered the standard patient‐centred outcome report by the International Consortium for Health Outcomes Measurement . We have transitioned to the EPIC score in recent years to facilitate comparison between studies and comply with recommendations of other groups .…”
Section: Discussionmentioning
confidence: 99%